1977
DOI: 10.1111/j.1471-0528.1977.tb12521.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor Viii‐related Antigen and Factor Viii Coagulant Activity in Normal and Pre‐eclamptic Pregnancy

Abstract: The changes in the ratio between factor VIII-related antigen and factor VIII activity were compared in ten patients with normal pregnancies and in ten patients with severe pre-eclampsia. In the patients with pre-eclampsia, a highly significant increase in the ratio was observed during the third trimester. No difference in the ratio between the two groups was found on day 7 of the puerperium. In the pre-eclamptic patients, the highest ratios for factor VIII-related antigen to factor VIII activity were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
3

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 8 publications
2
11
3
Order By: Relevance
“…While factor VIII activity and fibrinogen concentrations have not been considered to be of great value in this regard, the VWAg/ FVIII ratio has been reported to show a significant increase in PE (11,13,18). By comparison, in this study rises were found in both factor VIII and von Willebrand antigen concentrations from both normal and preeclampsia subjects with a nonsignificant effect on the VWAg/FVIII ratio.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…While factor VIII activity and fibrinogen concentrations have not been considered to be of great value in this regard, the VWAg/ FVIII ratio has been reported to show a significant increase in PE (11,13,18). By comparison, in this study rises were found in both factor VIII and von Willebrand antigen concentrations from both normal and preeclampsia subjects with a nonsignificant effect on the VWAg/FVIII ratio.…”
Section: Discussioncontrasting
confidence: 57%
“…In cases of preeclampsia, von Willebrand's antigen has been observed to rise both during pregnancy and after delivery, certainly in excess of rises in factor VIII activity, which in some cases fell (10)(11)(12)(13)(14). This resulted in a significant increase in the VWAg/FVIIIC ratio.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the 1970s and 1980s, several authors reported an elevated ratio of VWF/FVIII:C during pregnancy and an even higher ratio in pregnancies complicated by pre-eclampsia [26][27][28][29] and hypertension [30,31]. Altered coagulation status due to these conditions might increase the factor VIII:C consumption, causing plasma FVIII:C levels to go down.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy is a stressful condition characterized by SRM hyperactivity that elevates blood levels of Factor VIII, generates insoluble fibrin, and increases blood viscosity and coagulability [156,175,194,657,658,662,663]. This is partially offset by Hemodilution anemia during pregnancy that increases blood turbulence and inhibits atherosclerosis [7,8] Eclampsia increases the risk of DIC, especially in the presence of amniotic fluid embolus.…”
Section: Eclampsia and Amniotic Fluid Embolusmentioning
confidence: 99%